Música na Mitolologia Tenetehara - Heber Fernandes Negrao (2008)
This is a bibliography research about the Tenetehara, a Tupi language people who live in the West Amazon. The aim of this work is to deal with the relation between native music and myths of these people. The ethnography is based on a large bibliography since there was not an opportunity to make a field research. This dissertation presents important issues for Brazilian ethnology discussion. After, these issues are correlated with the music and myths of Teneteharas society.